Global System Fof Mobile-Based Data Acquisition For Monitoring Of Power Distribution System - Kassim, Mubashar M. B. (2008)

(untitled)
Modern electrical distribution systems are monitored and controlled remotely using Supervisory Control and Data Acquisition (SCADA) System. A control center that receives on-line information about the network must control and monitor the medium and large power distribution system that usually covers large geographical area. GSM network currently covers almost all the parts of the country and this makes it possible in terms of feasibility to place and collect data from distribution power system using this communication network which reduces the cost of establishing the system communication for large geographical area like the distribution of power system. A prototype of power factor correction and remote data acquisition with control center based GSM network has been presented in this thesis. The operating parameters of the power distribution system have been monitored in the control center beside the operation of the power factor correction. The proposed design of the prototype integrate sensors package with GSM controller which was programmed using Java to Micro Edition (J2ME). The GSM controller was programmed to control the power factor and send the acquired information to store it in the database of the control center. This database will be a useful source for the utility of distribution system after analyzed it to help the distribution system in monitoring the operational behavior and identify faults before any problem failure thus resulting in significant cost saving beside the improve of system reliability. The measurements obtained have a small error when compared to previous work. The error was 6 mV on a 5000mV scale while the previous work of Al_Ali et al., (2004(a)) was 10 mV on the same scale. By sending and receiving Short Message Service (SMS), the system achieves the functions of data transmitting, data processing, system diagnosing, alarm sending and report generating.